Construction of a thermally conductive network to improve the thermal and mechanical performance of silicone rubber foam - Hongjie Xie; Lijuan Zhao; Yanli Chen; Bing Han; Yu Hua; Dongliang Zhang; Zhaoqiang Li; Qibo Deng; Yunfeng Zhao (eXPRESS Polymer Letters, 2023)
Silicone foam (SF) is a porous silicone rubber with a lower density, higher elasticity, and good thermal stability. In this work, we selected aluminum spheres and carbon fiber (CF) as thermally conductive fillers to prepare hybrid SF. After optimization, we found that Al and CF hybrid SF (Al-CF-SF) has a higher thermal conductivity (1.37 W·m–1·K–1) than the single-filler filled SF (CF-SF, 1.2 W·m–1·K–1 or Al-SF, 0.52 W·m–1·K–1) under the same filling amount of 60 wt%. The finite element simulation was used further to explore the thermal conductive mechanism of the hybrid SF. Meanwhile, the compressive and tensile modulus of the material (CF-SF) was increased to 10.8 and 3.3 MPa compared with pure SF, respectively, and the mechanical properties were improved. In addition, infrared thermography further demonstrated that Al-CF-SF has a faster heat transfer rate under relaxation and applied pressure.